Remythology and Ideology of Nyonya Muluk in Masmundari’s Damar Kurung Painting - Aniendya Christianna; Acep Iwan Saidi; Riama Maslan Sihombing; Nuning Yanti Damayanti (Universitas Airlangga, 2022)
This study aims to explore the visualization of damar kurung's painting with Nyonya Muluk theme and its meaning in the context of Javanese culture critically. It was stated that the figure of Nyonya Muluk was inspired by Masmundari's experience of meeting the Queen of the Netherlands who had visited Surabaya. Nyonya Muluk is described as a large woman who wears a dress and jewelery and has a pair of wings. Around her are other human figures painted in smaller sizes. To pursue the aim this study, the analysis was conducted using Gillian Rose's visual methodology which takes the position of the site of self. The analysis of this study found how Masmundari depicts objects by combining opposing cultural elements reflecting that the postcolonial subject is never completely the position of the colonized or the colonizing self. The ambivalence that arises in the practice of mutual views shows a form of negotiation or resistance from the colonized position. Masmundari's remitology also depicts the Indonesian nation as a colonized party trying to decolonize itself from colonial rule. By relocating the mythology of Nyonya Muluk in a contemporary context, this painting shows the efforts of the Indonesian people to regain 'independence' by using local traditions to fight against the culture imposed by the colonialists. In short, it can be concluded that the remitology of Nyonya Muluk in amar kurung's painting not only reflects Masmundari's resistance to Western colonial and post-colonial rule, but also represents Masmundari's resilience to the definition of her identity as Javanese.